2020
DOI: 10.3390/diagnostics10070504
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Cell Death Responses in Fibrotic Lung Disease: Crosstalk between Structured and Non-Structured Cells

Abstract: Fibrosis is a life-threatening disorder caused by excessive formation of connective tissue that can affect several critical organs. Innate immune cells are involved in the development of various disorders, including lung fibrosis. To date, several hematopoietic cell types have been implicated in fibrosis, including pro-fibrotic monocytes like fibrocytes and segregated-nucleus-containing atypical monocytes (SatMs), but the precise cellular and molecular mechanisms underlying its development remain unclear. Repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 105 publications
(134 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, direct mucosal exposure to fluoride causes tissue damage, including to the oral mucosa 24 that may relate to OSMF's postulated defective wound healing pathogenesis 25,26 following chronic injury. Specifically, repetitive injury triggers extensive apoptosis in the epithelium 27 . This induces proliferation of activated myofibroblasts and fibrotic lesion formation, representing critical epithelium‐myofibroblast interactions driving fibrosis 27 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, direct mucosal exposure to fluoride causes tissue damage, including to the oral mucosa 24 that may relate to OSMF's postulated defective wound healing pathogenesis 25,26 following chronic injury. Specifically, repetitive injury triggers extensive apoptosis in the epithelium 27 . This induces proliferation of activated myofibroblasts and fibrotic lesion formation, representing critical epithelium‐myofibroblast interactions driving fibrosis 27 …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, repetitive injury triggers extensive apoptosis in the epithelium. 27 This induces proliferation of activated myofibroblasts and fibrotic lesion formation, representing critical epithelium-myofibroblast interactions driving fibrosis. 27 Therefore, based on the above observations and preliminary results of the present study, we hypothesize that fluoride elicits profibrotic effects through several mechanisms (Figure 4).…”
Section: Statistical Analysis (Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary fibrosis (PF) is a chronic and progressive lung disease characterized by abnormal inflammatory wound healing and excessive deposition of extracellular matrix (ECM) [ 87 ]. Studies indicate that CXC chemokines and CXCRs play a role in PF.…”
Section: The Role and Therapeutic Relevance Of CXC Motif Chemokines A...mentioning
confidence: 99%
“…CXCL12 acts through CXCR4, a receptor with a role in many biological processes including bone marrow- (BM-) derived stem cell activation and mobilization [ 90 ]. Fukushima et al [ 87 ] identified RNA-binding protein 7 (RBM7) and CXCL12 as important components of fibrosis development as both are enhanced in the fibrotic phase. RBM7 orchestrates a cascade of apoptotic events in the lung epithelium as a result of nuclear degradation of NEAT1 noncoding RNA (ncRNA).…”
Section: The Role and Therapeutic Relevance Of CXC Motif Chemokines A...mentioning
confidence: 99%